Effects of using assistive devices on the components of the modified instrumented timed up and go test in healthy subjects - Abualait, Turki S.; Alnajdi, Ghazi K. (Heliyon, 2021)
Evaluation of the changes in gait spatiotemporal parameters and functional mobility with using assistive devices (ADs) would provide useful information and mutual assistance when prescribing such ambulatory devices. This study aimed to investigate the spatiotemporal gait and functional mobility parameters in healthy adults when walking using different ADs. A group of healthy subjects participated in the study. The instrumented modified Timed Up and Go test (iTUG) was used to investigate the impact of different types of ADs on spatiotemporal and functional mobility parameters. Subjects showed a significant difference in the gait task performance (P = .001) in stride velocity, stride length, and cadence when walking with and without ADs. A significant difference was also found in the performance of the turn-to-sit task (P = .001) in both velocity and duration when walking with and without ADs. The time to complete sit-to-stand was significantly slower when using a walker (98.3 ± 22.3°/sec, P = .004) and a cane (78.2 ± 21.9°/sec, P = .004) compared to walking without an AD (78.2 ± 21.8°/sec). No significant difference was found between walking with a cane group versus walking with a four-wheeled walker group (P = .94). ADs altered gait and functional mobility parameters differently in healthy subjects. Using a four-wheeled walker showed a tendency to increase stride velocity, cadence, stride length, and slow sit-to-stand velocity compared to using a cane. The findings highlight using more caution clinically when prescribing ADs and providing gait training. Spatiotemporal gait parameters, Functional mobility, Assistive devices, Modified instrumented timed up and go test